Synergistic cytotoxic effects of combined δ-tocotrienol and jerantinine B on human brain and colon cancers - Abubakar, I.B.; Lim, K.H.; Kam, T.S.; Loh, H.S. (Elsevier, 2016)
Ethnopharmacological relevance The genus Tabernaemontana has widespread distribution throughout tropical and subtropical parts of the world, i.e. Africa, Asia and America which has long been used for treatments of different disease conditions including tumours, wounds, syphilis, stomach ache and headache. Some Tabernaemontana species are used for treatment of piles, spleen and abdominal tumours in India. In particular, the leaf of Tabernaemontana corymbosa is used for treatment of tumours in Bangladesh. Parts of the plant or whole plants are used as decoctions, steam bath, powder and ointments. Aim of study The present study was undertaken to study the mechanism of apoptosis induction in human glioblastoma (U87MG) and colorectal adenocarcinoma (HT-29) cancer cells by a novel indole alkaloid, jerantinine B isolated from T. corymbosa, δ-tocotrienol and the combined low-dose treatments of δ-tocotrienol with IC20 dose of jerantinine B. Materials and methods Cell viability, isobologram and combinational index (CI) analyses were used to determine the pharmacological interaction between combined treatments based on the IC50 values obtained. Fluorescence and histochemical staining techniques as well as comet assay were used for evaluating the morphological changes and DNA damage pattern, respectively. The effects of treatments on microtubules, caspase activity and cell death were determined using immunofluorescence technique, caspase colorimetric and neutral red uptake assays, respectively. Results Jerantinine B, δ-tocotrienol and combined low-dose treatments induced a dose-dependent growth inhibition against U87MG and HT-29 cells selectively with less toxicity acted towards the normal MRC5 cells. Synergistic growth inhibition observed with CI values of 0.85 and 0.77 for U87MG and HT-29 cells, resulting in up to 2-fold and 3.8-fold dose reduction of δ-tocotrienol and jerantinine B, respectively. U87MG and HT-29 cells exhibited morphological features of apoptosis and double stranded DNA breaks. Individual and combined treatments induced caspase 8 and 3 activities and cell death independent of caspase activation on U87MG and HT-29 cells. An increased caspase 9 activity was also evident on U87MG and HT-29 treated with combined treatments and HT-29 cells treated with jerantinine B. Jerantinine B and combined low-dose treatments with δ-tocotrienol undoubtedly disrupted the microtubule networks. Conclusion The present study demonstrated the mechanism for cytotoxic potency of δ-tocotrienol and jerantinine B against U87MG and HT-29 cells. Furthermore, combined low-dose treatments induced concurrent synergistic inhibition of cancer cell growth with concomitant dose reduction thus minimizing toxicity to normal cells and improving potency of δ-tocotrienol and jerantinine B.